The Evaluation of the national Struggle of the Risorgimento famous figures in ’’ The Mshak’’ - Movsisyan, Feliqs (History and Culture, 2022)
The Italian Risorgimento, which aimed to overthrow the Austrian rule and unite Italy, found a wide response in the Armenian public thought of the time and in the periodical press. Reflecting on this, “Mshak” newspaper, the pioneer of the Armenian liberal current, highlighted the role of Risorgimento leaders Giuseppe Mazzini, Giuseppe Garibaldi, King Victor Emmanuel II and Count Camillo Cavour in the unification of Italy. The newspaper calls G. Mazzini “prominent republican”, “democratic genius” and “great patriot”, who had been fascinated by the idea of ​​freedom and union of his homeland since his student years. In particular “Mshak” newspaper highly appreciates G. Garibaldi’s contribution to the struggle for the unification of Italy, calling him “a great Italian patriot” who immortalized his name with his services to the motherland. According to the description of the newspaper, G. Garibaldi constantly invited his compatriots to fight for freedom and showed them a personal example of “unshakable determination”. “Mshak” characterizes King Victor Emmanuel II as “an outstanding patriot and an outstanding statesman”, a patriot and brave soldier, a king guided by the interests of the people and the state. According to the opinion of the newspaper, the king was a cautious person, he never took a decisive step, he allowed popular hero G. Garibaldi to start the struggle every time. In this way, he united Italy, which he considered the goal of his life. According to “Mshak”, Victor Emmanuel’s “name occupies a glorious place in the history of Italy”. “Mshak” also highlights C. Cavour in the Italian liberation struggle. According to the newspaper, King Victor Emmanuel was always guided by C. Cavour’s advice and “he is beholden to him most of his successes”.